Social Norms and Conditional Corruption: The Case of Lebanon - Haykal, Sarah Hariri (European Scientific Journal, ESJ, 2017)
This paper explains the emergence of a conditional norm of corruption on an mesosocial level between culture and structure. It considers corruption as a result of interactions between individuals through social norms. In a game theory perspective, we show that the tolerance of corruption is dependent on the social norms generated by mutual betting on other people’s behavior in society. Players tend to align their own strategy with the strategy of others. Therefore, a social norm of corruption is determined by the proportion of players who adopt a corruption strategy. The choice between corruption and honesty depends on a specific social norm. Analysis of corruption in Lebanon shows that corruption as a phenomenon is contagious and frequent to the point of tolerating it as a social norm.